1999
DOI: 10.1046/j.1365-2702.1999.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of information giving for patients newly diagnosed with cancer: a review of the literature

Abstract: The importance of information giving has been recognized and promoted in political, ethical and professional arenas and this has ultimately resulted in the publication of a vast amount of literature relating to the subject. This literature review considers the functions of patient information and the factors influencing information seeking for patients who have been diagnosed with cancer. Methods of providing information are discussed and the nurse's role in information giving is examined. A number of core pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
232
0
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(267 citation statements)
references
References 41 publications
7
232
0
16
Order By: Relevance
“…In consistence with this Mills and Sullivan (1999) reported that younger patients were requesting more information needs than older patients.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…In consistence with this Mills and Sullivan (1999) reported that younger patients were requesting more information needs than older patients.…”
mentioning
confidence: 53%
“…Many factors would have an impact on patients information needs and no prescriptive/ one method would be applied for all/ one method does not fit all. Therefore different method should be used based on patients' information needs and characteristics (Mills and Sullivan, 1999). Having one designated member of your treatment team with whom you can talk about all aspects of cancer, treatment and follow-up 3.6±0.7 3.7±0.6 Being informed about things you can do to help yourself get well 3.6±0.6 3.7±0.6 Being given written information about important aspects of care 3.6±0.8 3.6±0.7 Being given explanations about tests and test results 3.7±0.7 3.6±0.5 Being adequately informed about the benefits and side-effects of treatments before you have to choose them 3.6±0.8 3.7±0.6 Having access to professional counseling if you need it 3.3±1.07 3.3±0.8 Being given information about aspects of managing your illness and side effects at home 3.1±1.0 3.2±1.2 Being informed about support groups and sources in your area 2.9±1.12 3.0±0.9 The opportunity to talk to someone who understands and has been through a similar experience 2.3±1.13 2.8±1.02 Being given information about sexual problems that may be caused by your cancer or treatment 2.9±1.2 ** *Scaled as "1 = not important" to " 4 = very important", **this item has not been asked want to get information about disease which disturbs me", whereas majority of relatives agreed (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed, graphical signage is often designed to help people understand the requirements of unfamiliar situations, which can lead to greater empowerment and a sense of control. In a healthcare context, well-designed booklets and information leaflets can not only make patients aware of facts and give advice, but also encourage discussion and prompt questions [12]. Furthermore, leaflets that encourage patients to raise issues and discuss symptoms in the consultation process can improve patient satisfaction and perceptions of communication [13].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Access to information assists patients to cope with stressful situations by giving them a sense of control and enabling them to actively participate in decision making, and being well informed reduces distress and increases satisfaction with care. 20,21 Health professionals within treatment centres are the preferred information source, with written information being a popular back-up to verbal information and advice from health care staff. 22 Written information is also a valuable source of information for family and friends who provide care outside the hospital setting.…”
Section: Discussionmentioning
confidence: 99%